Examination of the Conversations in a WhatsApp Group Created for Communication in a Bachelor’s Level Astronomy Course - Kurnaz, Mehmet Altan; Ezberci̇ Çevi̇k, Ebru; Yuzbasioglu, Hafife Bozdemir; Helvaci, Sevcan Candan (ISTES Organization, 2020)
The aim of this research on an astronomy course is to examine the situations that arose when WhatsApp, a social media application, was used as a tool for cooperation and interaction. In this work, a case study design was adopted. The WhatsApp group created for the research was composed of 87 participants and the messages exchanged in the WhatsApp group were used as research documents. Data were analyzed through descriptive and content analysis methods. The sharing in the WhatsApp group and the topics of the messages were revealed in the content analysis. The research results showed that the students used the WhatsApp group as an interaction tool in an extracurricular environment. It was also determined that they used this platform in order to inform each other about daily events and share and discuss information.
Keywords: 4. Education